2020
DOI: 10.1021/acs.biomac.0c01408
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Hydrogel Composition and Geometry on Human Mesenchymal Stem Cell Osteogenesis

Abstract: Microgels are emerging as an outstanding platform for tissue regeneration because they overcome issues associated with conventional bulk/macroscopic hydrogels such as limited cell−cell contact and cell communication and low diffusion rates. Owing to the enhanced mass transfer and injectability via a minimally invasive procedure, these microgels are becoming a promising approach for bone regeneration applications. Nevertheless, there still remains a huge gap between the understanding of how the hydrogel matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…These studies suggest that some cells are more vulnerable when exposed to fluid shear than others 32,33 suggesting that the effects should be verified for each individual cell type tested. However, in our previous work, the flow rate ratio of 4:1 mL −1 (oil versus hydrogel phase) was applied to several cell types (mesenchymal stromal cells, 5,26 human fetal chondroprogenitor cells, 29 human articular chondrocytes, 29 CAR-T cells, 27 coculture of hematopoietic stem cells, and OP9-DL cells (bone marrow stromal cells transduced to express the Notch ligand, Delta-like 1 or 4)) 22 without any negative effects on cell viability. A further reduction in microgel size was achieved by using minimal ID tubing (1.44 mm), which allowed the 33G needle to be used (Figure 4D).…”
Section: Anticipated Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies suggest that some cells are more vulnerable when exposed to fluid shear than others 32,33 suggesting that the effects should be verified for each individual cell type tested. However, in our previous work, the flow rate ratio of 4:1 mL −1 (oil versus hydrogel phase) was applied to several cell types (mesenchymal stromal cells, 5,26 human fetal chondroprogenitor cells, 29 human articular chondrocytes, 29 CAR-T cells, 27 coculture of hematopoietic stem cells, and OP9-DL cells (bone marrow stromal cells transduced to express the Notch ligand, Delta-like 1 or 4)) 22 without any negative effects on cell viability. A further reduction in microgel size was achieved by using minimal ID tubing (1.44 mm), which allowed the 33G needle to be used (Figure 4D).…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…We have primarily used hydrogels formed from norbornene-functionalized gelatin cross-linked with thiol-functionalized poly­(ethylene glycol), PEG. , These polymers can be cross-linked under blue (400–500 nm) or UV light (365 nm) in the presence of a biocompatible photoinitiator, lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP), affording robust hydrogels. The gelatin provides cell recognition function for cell adhesion and remodeling, while the PEG improves the mechanical properties, enabling a highly biocompatible system that has been proven to support cell viability and function. , However, other polymer formulations, such as the inclusion of functionalized hyaluronic acid are possible, providing the hydrogel precursor can flow through the device and be cross-linked by light postmicrogel fabrication. The procedure can also be adapted for varying cell types. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the solution was lyophilized to obtain norbornene-conjugated gelatin. Thiol modified linear PEG (PEG(SH) 2 ) was synthesized via a three-step route based on our previously reported protocol [ 26 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Through anodization and subsequent dip coating treatment, two highly ordered nano-pits with two different sizes were successfully constructed on the surface of 316LSS and then stimulated osteogenesis and angiogenesis ( Ni et al, 2020 ). Shrestha et al (2020) also found that both the composition and form of the hydrogel can determine the success of tissue formation, and these two factors have a complex interaction with cell behavior and matrix deposition. This has important implications for tissue engineering.…”
Section: Introductionmentioning
confidence: 96%